2013
DOI: 10.1037/a0034197
|View full text |Cite
|
Sign up to set email alerts
|

Mind-wandering and falls risk in older adults.

Abstract: While mind-wandering is common, engaging in task-irrelevant thoughts can have negative functional consequences. We examined whether mind-wandering frequency may be related to falls -a major health care problem. Seniors completed a sustained attention task and self-reported their current attentional states. Monthly falls reports were collected over 12 months. Falls were associated with an increased frequency of mind-wandering. Additionally, poorer performance on the sustained attention task was associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 61 publications
0
21
0
Order By: Relevance
“…Indeed, previous research has pointed towards an association between attentional deficits and falls (Nagamatsu et al, 2009, 2013). We highlight, however, that we did not observe between-group differences on task accuracy during the Flanker task.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, previous research has pointed towards an association between attentional deficits and falls (Nagamatsu et al, 2009, 2013). We highlight, however, that we did not observe between-group differences on task accuracy during the Flanker task.…”
Section: Discussionmentioning
confidence: 99%
“…First, interest in the general topic of spontaneous cognition has increased rapidly during recent years in both psychology and neuroscience (e.g., Andrews-Hanna et al, 2010; Christoff et al, 2011; O'Callaghan et al, 2015; Smallwood & Schooler, 2015), and the trend seems likely to continue. Second, the emergence of studies on MW in older adults during the past few years (e.g., Jackson & Balota, 2012; Krawietz et al, 2012; Maillet & Rajah, 2013; Nagamatsu et al, 2013; Staub et al, 2014) suggests an increasing focus on spontaneous cognition among cognitive aging researchers. Third, although studies of different spontaneous thought types are typically pursued independently of one another, we think that it is useful to consider them together in order to encourage questions and future investigations about similarities and differences among these processes as a function of aging.…”
Section: Introductionmentioning
confidence: 99%
“…Since the publication of this review, Mrazek, Phillips, et al (2013) have similarly reported impaired reading comprehension associated with prompt-assessed mind-wandering. A number of further studies have found additional costs: attentional lapses associated with impaired performance on the Stroop task (Unsworth & McMillan, 2014), a significant relationship between mind-wandering proclivity and frequency of falls in older adults, presumably at least partly because of inattention to external stimuli (Nagamatsu et al, 2013), particularly in the left visual field (Kam, Nagamatsu, & Handy, 2014), and reduced empathic responses to others' physical discomfort, as assessed by participants' ratings and electrophysiologically with event-related potentials (Kam, Xu, & Handy, 2014). By contrast, when leaving aside its perseverative, ruminative forms, mindwandering appears unrelated to most measures of health Ottaviani, Shapiro, & Couyoumdjian, 2013).…”
Section: Costs Of Spontaneous Thoughtsmentioning
confidence: 99%